Relationship basic beliefs with values and fears of students with different levels of psychological security - Blahenkova, Natallia P. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
The problem of psychological safety and the role of basic beliefs in its maintenance are considered. The basic beliefs of students and the general level of their psychological safety are characterised. The results of the study of students’ fears and values are presented. The article analyses the relationship between basic beliefs and experienced fears and values among students with different levels of psychological safety.